MOTILITAS DAN VIABILITAS SPERMATOZOA MENCIT JANTAN (Mus musculus L.) SETELAH PEMBERIAN EKSTRAK DAUN KUMIS KUCING ( Orthosiphon aristatus) - Ayesa, Putri; Fadhil Ramadhan, Bintang; Fitria, Davina; Mutia, Ravena; Ahda, Yuni; Atifah, Yusni (Universitas Cokroaminoto Palopo, 2025)
This study aims to evaluate the effect of cat whisker leaf extract (Orthosiphon aristatus) on motility and viability of male mice spermatozoa (Mus musculus L.). The research method used was experimental. This study was conducted to determine the effect of the treatment given to a matter under study. Consists of three treatments, namely control (without treatment), treatment dose 0.5 mg and treatment dose 0.8 mg Cat whisker leaf extract is given orally for 15 days. After treatment, spermatozoa were taken from the epididymis of male mice and tested for motility and viability using statistical analysis through the One-Way Anova test. The results showed that the decrease in motility and viability of spermatozoa depended on the dose given. The higher the dose of cat whisker extract, the motility and viability of spermatozoa decreased. In mice with a dose of 0.8 mg spermatozoan motility is silent and does not move and for viability it dies. The control treatment showed different motility but remained alive with good viability. Meanwhile, the treatment group showed a decrease in motility and viability, with control mice.